Pengaruh Lokasi Toko dan Citra Merek terhadap Minat Beli Konsumen pada Ayam Gepuk Pak Gembus Padang - Febsri Susanti; Zaky Zakaria (JURNAL PUNDI, 2019)
The current development of business competition in Indonesia is very tight, which makes companies do various ways to attract consumers to buy their products. This study aims to determine whether the location of the store and brand image influence consumer buying interest in the Ayam Gepuk Pak Gembus, by using data collection methods in the form of a questionnaire of 160 respondents. In analyzing the data using validity, reliability, and classic assumption tests, namely normality, multicollinearity and heteroscedasticity. The analytical method used is multiple linear regression analysis. While for testing the hypothesis, namely the F test, T test, R2 determinant coefficient using SPSS tools. The results of the tests conducted found that the location of the store had a positive and significant effect on consumer buying interest and the brand image also had a positive and significant effect on consumer buying interest.